2021
DOI: 10.1038/s41598-021-81143-5
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the trends and variability in the United States tornado records using climate teleconnections and shifts in observational practices

Abstract: The annual frequency of tornadoes during 1950–2018 across the major tornado-impacted states were examined and modeled using anthropogenic and large-scale climate covariates in a hierarchical Bayesian inference framework. Anthropogenic factors include increases in population density and better detection systems since the mid-1990s. Large-scale climate variables include El Niño Southern Oscillation (ENSO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Pacific Decadal Oscillation (PDO), Arct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
(99 reference statements)
0
12
0
Order By: Relevance
“…Brown and Nowotarski (2020) reported that daily values of the NOAA/Climate Prediction Center AO index were relevant to tornado outbreak likelihood in the southeastern US across all seasons. Nouri et al (2021) found a positive relation between annually averaged state tornado frequencies and the AO. While only suggestive, the tornado report numbers in early 2021 are not inconsistent with the concurrent values of the AO index: February −1.191, March 2.109, April −0.204, and May −0.161 (NOAA Climate Prediction Center, 2022b).…”
Section: Introductionmentioning
confidence: 84%
“…Brown and Nowotarski (2020) reported that daily values of the NOAA/Climate Prediction Center AO index were relevant to tornado outbreak likelihood in the southeastern US across all seasons. Nouri et al (2021) found a positive relation between annually averaged state tornado frequencies and the AO. While only suggestive, the tornado report numbers in early 2021 are not inconsistent with the concurrent values of the AO index: February −1.191, March 2.109, April −0.204, and May −0.161 (NOAA Climate Prediction Center, 2022b).…”
Section: Introductionmentioning
confidence: 84%
“…Moreover, Elsner et al [40] showed the connection between a positive phase of the North Atlantic Oscillation (NAO) and a lower tornado activity across southeastern states. Another recent study [41] also showed that NAO negatively influences annual tornado frequency. Knowing that the winter index of NAO (December to March) during mid-1970s to early-2000s was primarily in its positive phase [42], we can also associate less frequent LTOs with the positive phase of NAO.…”
Section: Lto Return Timementioning
confidence: 89%
“…The reason for the shift in southern Ontario tornado frequency to later in the season is not clear, especially given no such shift is apparent for neighboring US states. One would assume that if the shift relates to global atmospheric teleconnections such as the El Niño–Southern Oscillation and the North Atlantic Oscillation (see Nouri et al., 2021, for further details on teleconnections and tornadoes), then the effect would be periodic and seen over a larger region than just southern Ontario. It is known that the Great Lakes have been gradually warming over at least the last several decades—since reliable buoy observations began (e.g., Dobiesz & Lester, 2009; O’Reilly et al., 2015).…”
Section: Discussionmentioning
confidence: 99%